Abusive and Compassionate Supervision as Predictors of Turnover Intention: Job Satisfaction Mediation in Smartphone Retail - Ageng Fitra Aidin; Dedi Muhammad Sidiq; Tonny Todokonyero; Nhan Cam Tri (Media Ekonomi dan Manajemen, 2026)
This study examines the effects of abusive supervision and workplace compassion on turnover intention, with job satisfaction as a mediating variable, among employees in Indonesia’s smartphone retail industry. Although previous studies have extensively investigated abusive supervision and organisational support, the role of workplace compassion as a counterbalancing organisational resource remains underexplored in the retail sector. Data were collected through a survey of 140 frontline employees, including sales staff and product promoters, in a smartphone retail company in Cirebon, Indonesia. The data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings indicate that abusive supervision negatively affects job satisfaction and positively affects turnover intention, whereas workplace compassion positively influences job satisfaction and reduces turnover intention. Furthermore, job satisfaction significantly mediates the relationships between abusive supervision, workplace compassion, and turnover intention. The findings highlight the importance of compassionate workplace practices and supportive leadership in enhancing employee satisfaction and reducing turnover intentions. This study contributes to the organisational behaviour literature by demonstrating the role of workplace compassion as a valuable organisational resource for employee retention in high-pressure retail environments.